Real-world practice patterns for patients with advanced non-small cell lung cancer: multicenter retrospective cohort study in Japan - Isobe H; Mori K; Minato K; Katsura H; Taniguchi K; Arunachalam A; Kothari S; Cao X; Kato T (Lung Cancer: Targets and Therapy, 2017)
Hiroshi Isobe,1 Kiyoshi Mori,2 Koichi Minato,3 Hideki Katsura,4 Kazuko Taniguchi,5 Ashwini Arunachalam,6 Smita Kothari,6 Xiting Cao,6 Terufumi Kato7 1Department of Medical Oncology, KKR Sapporo Medical Center, Hokkaido, 2Department of Thoracic Diseases, Division of Thoracic Oncology, Tsuboi Cancer Center Hospital, Fukushima, 3Department of Respiratory Medicine, Gunma Prefectural Cancer Center, Gunma, 4Division of Respiratory Medicine, Tokyo Women’s Medical University Yachiyo Medical Center, Chiba, 5Market Access, MSD K.K., Tokyo, Japan; 6Center for Observational & Real World Evidence (CORE), Merck & Co., Inc., Kenilworth, NJ, USA; 7Department of Respiratory Medicine, Kanagawa Cardiovascular and Respiratory Center, Kanagawa, Japan Background: Recommended therapies for advanced/metastatic non-small cell lung cancer (NSCLC) have changed with the advent of targeted therapies. The objectives of this retrospective chart review study were to describe treatment patterns, biomarker testing practices, and health care resource use for advanced NSCLC at 5 sites in Japan.Patients and methods: We studied anonymized medical record data of patients aged ≥18 years who initiated systemic therapy for newly diagnosed stage IIIB or IV NSCLC from January 2011 through June 2013. Data were analyzed descriptively by histology and mutation status. Overall survival was estimated using the Kaplan–Meier method. Results: We studied 175 patients, including 43 (25%), 129 (74%), and 3 (2%) with squamous, nonsquamous, and unknown NSCLC histology, respectively; 83% had stage IV NSCLC. Overall, 123 patients (70%) were male; the median age was 70 years (range, 47–86); and 33 (19%) were never-smokers. In the nonsquamous cohort, 105 (81%) and 25 (19%) of patients were tested for epidermal growth factor receptor (EGFR) mutation and anaplastic lymphoma kinase (ALK) rearrangement, respectively; 44 (42%) had EGFR-positive NSCLC and 2 (8%) had ALK-positive NSCLC, including 26/46 (57%) women and 21/46 (46%) never-smokers. In the squamous cohort, 17 (40%) and 4 (9%), respectively, were tested; 1 EGFR-positive tumor was detected. After first-line therapy, 105 (60%) patients received second-line, and 54/105 (51%; or 31% overall) received third-line therapy. EGFR tyrosine kinase inhibitors were most commonly prescribed for EGFR-positive NSCLC across all lines. In the nonsquamous EGFR/ALK-negative/unknown cohort, most received first-line platinum combinations, particularly younger patients (78% ≥75 years vs 93% <75 years old). The average hospitalization was 21 days/admission. The median (95% CI) overall survival from start of first-line therapy was 9.9 months (7.6–11.7) for all patients and 17.9 months (9.9–24.4) for patients with EGFR/ALK-positive status.Conclusion: Biomarker testing is common for nonsquamous NSCLC at the 5 Japanese study sites. Treatment is personalized by mutation status and age, per guideline recommendations. Keywords: predictive biomarker, health care resource use, Japan, non-small cell lung cancer, systemic therapy, treatment patterns